EVALUASI KESESUIAN PEMANFAATAN AREA RUANG PUBLIK DENGAN RTRW DI KOTA TEGAL - Sandi, Zuhdan Ari (Geo-Image, 2016)
The purpose of the study are to: . Evaluate the implementation of the use of public space areas of the Spatial Tegal years 2010 to 2015 by using SIG.2. Knowing the distribution and extent of public space area Tegal. The research method is descriptive. The data analysis technique used is Descriptive Analysis, Spatial Analysis, Evaluation Quantity Green Open Space. The results showed the results of which have been digitized RTH in check through the field and digitization generate 138,910.23 m2 or 13.98 hectares and the area is 3,968 hectares Tegal this result Tegal green space in the city has an area of 0.4% with RTRW with the Spatial existing and Field actual area 116 783 m2 or 11.67 hectares with this result does not match the existing Spatial.